Arte para conocer y cambiar el mundo. Propuesta educativa desde una perspectiva sociológica - Megías Martínez, Clara (Arte, Individuo y Sociedad, 2007)
Nowadays, Internet and mass media development have caused a radical change in communication in Western World. Written language is giving way to visual language. Businessmen and publicists profit of the power of images to transmit messages, bombing us with all kinds of visual products and contributing to the creation of a passive and manageable receiver. We are living in a period of history characterized by individualism and no ideals. But, in contrast, with the development of the multimedia world, many users create their own personal spaces to express their opinions. Receivers also demand an active role in the process of communication. Creative citizenship and new artistic groups show us what we can achieve with commitment and participation. In this article we will analyse the necessity of a kind of educative action that demands a critical and reflective use of visual language. From artistic education we can propose creative activities that help us understand the world and change what we do not like from it.